The effect of mind–body exercise on cognitive function and neuroplasticity in elderly people with mild cognitive impairment: a systematic review and meta-analysis - Tian, Huifang; Yang, Xi; Li, Jiahuan; Cheng, Yuqi; Tian, Shui; Meng, Fanfan; Zhu, Qinqin; Shen, Ying; Wang, Tong; Guo, Chuan; Zhu, Yi (Frontiers in Aging Neuroscience, 2025)
ObjectiveThis systematic review and meta-analysis aims to comprehensively analyze the effects of mind–body exercise on cognitive function, brain structure, and brain function in individuals with mild cognitive impairment (MCI) by assessing randomized controlled trials.MethodsA systematic search was conducted using four databases: Cochrane Library, EMBASE, PubMed, and Web of Science, from inception until December 2023. The study quality was assessed using the Cochrane risk-of-bias tool. Systematic review and meta-analyses were performed for outcome measures such as the Montreal Cognitive Assessment (MoCA), gray matter volume (GMV), functional connectivity at rest (rsFC), amplitude of low-frequency fluctuation (ALFF) and event-related potential (ERP) P300 latency. Three-dimensional coordinates of brain regions with notable variances were extracted from imaging and delineated in the brain map.ResultsAfter screening 433 studies, nine met the eligibility inclusion criteria. In 4 studies using the MoCA scale, meta-analysis showed a significant effect of aerobic exercise intervention on global cognitive function improvement (MD = 1.6; 95% CI: 0.70 to 2.50; p = 0.0005). Most of the included studies reported that mind–body exercise improved gray matter volume in the hippocampus, bilateral anterior cingulate gyrus, frontotemporo-occipital regions, altered functional connectivity of the default mode network (DMN) and dorsal attentional network (DAN), neural activity in key brain regions in older adults with MCI.ConclusionThis systematic review demonstrates that mind–body exercise is associated with improved cognitive function and neuroplastic changes in older adults with mild cognitive impairment, with changes particularly evident in regions vulnerable to neurodegeneration such as the hippocampus and anterior cingulate cortex.Systematic review registrationCRD42022251115; https://www.crd.york.ac.uk/PROSPERO/view/CRD42022251115.